An assessment of the impact of fast track land and agrarian reforms on food security in Umguza district - Ngwenya, Jobert (Midlands State University, 2017)
This study evaluates the effect of the Fast Track Land and Agrarian Reforms in Umguza District, Ward 10 Resettlement area as a case study and Ward 7 as a control area. The hypothesis is that the Fast Track Land and Agrarian Reforms have impacted positively on food security at household level. The research methodology employed is explained as well as the policy context for Land and Agrarian Reforms both on paper and practice, is reviewed. The study is underpinned by the Learning U Curve Theory. Food security issues are also reviewed at conceptual and national level. The implementation of the Fast Track Land Reform (FTLRP) and the successive agrarian reform strategies by the government of Zimbabwe and other stakeholders was assessed and an examination on whether the beneficiaries of these policies are food secure as compared to the pre-2000 period. From the literature reviewed, it became clear that the process for the attainment of effective food security is far too complex to happen overnight. The answers to the interview questions referred to in Appendix B are highlighted. The hypothesis is tested by analysing these answers and strategic and policy proposals are made to assist the identified stakeholders to achieve effective rural development in the light of food security and the land and agrarian reform programs. The research findings indicate that there has been marginal increase in food production since 2000 (though there are seasonal fluctuations hinged on the amount of rainfall received) but this has not translated to food secure households because availability of maize only means that the diet is mostly cereal based. Additionally, poor rainfall patterns and lack of funding for the reforms has generally impacted negatively to attainment of national food security. The final chapter highlights the main points raised throughout the study and conclusions and recommendations are made. These include an all stakeholders approach to rural development, setting up a secure land tenure system, development of infrastructure, irrigation development, input supply mechanisms, setting up of a strong agriculture market among other recommendations.